Work, employment and engagement conditions in a female‐dominated public service occupation after restructuring/outsourcing. Issue 5 (29th January 2018) - Kirton, Gill; Guillaume, Cécile
Abstract: Most research on the phenomenon of public service restructuring/outsourcing focuses on lower skilled work in peripheral activities and typically provides an overview of effects on work, employment and employment relations. Through an in‐depth case study of probation, the intention of this article is to explore professional worker experiences of the restructuring/outsourcing of a core public service activity where the workforce is female dominated. The article highlights three dimensions of job quality that all suffered deterioration—work, employment and engagement. The case of probation adds to evidence demonstrating that employees experience adverse effects even though transfer regulations and union agreements supposedly protect workers. Probation also stands as an exemplar of impoverishment processes in a female‐dominated occupation which reinforces the view that public services can no longer be relied upon to provide high‐quality jobs for highly qualified women.